TWNK in Parkinson's Disease: A Movement Disorder and Mitochondrial Disease Center Perspective Study. Issue 9 (6th July 2022) - Percetti, Marco; Franco, Giulia; Monfrini, Edoardo; Caporali, Leonardo; Minardi, Raffaella; La Morgia, Chiara; Valentino, Maria Lucia; Liguori, Rocco; Palmieri, Ilaria; Ottaviani, Donatella; Vizziello, Maria; Ronchi, Dario; et al.
Abstract: Background: Parkinsonian features have been described in patients harboring variants in nuclear genes encoding for proteins involved in mitochondrial DNA maintenance, such as TWNK . Objectives: The aim was to screen for TWNK variants in an Italian cohort of Parkinson's disease (PD) patients and to assess the occurrence of parkinsonism in patients presenting with TWNK ‐related autosomal dominant progressive external ophthalmoplegia ( TWNK ‐adPEO). Methods: Genomic DNA of 263 consecutively collected PD patients who underwent diagnostic genetic testing was analyzed with a targeted custom gene panel including TWNK, as well as genes causative of monogenic PD. Genetic and clinical data of 18 TWNK ‐adPEO patients with parkinsonism were retrospectively analyzed. Results: Six of 263 PD patients (2%), presenting either with isolated PD (n = 4) or in combination with bilateral ptosis (n = 2), carried TWNK likely pathogenic variants. Among 18 TWNK ‐adPEO patients, 5 (28%) had parkinsonism. Conclusions: We show candidate TWNK variants occurring in PD without PEO. This finding will require further confirmatory studies. © 2022 Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.